Spaces of early education and care: exploring ethos, choice and parental engagement - Sophie Smith (2018)
The Early Years period is increasingly acknowledged as an important building block for the successful education of the child. Political interest in the Early Years stems not only from envisaging early education as an investment to ensure responsible, productive and aspirational citizens, but also as a way of governing the family through forms of surveillance. Despite its importance, there is a paucity of academic research which examines the role Early Years education plays in social reproduction. This thesis fills this lacunae through an examination of the diversity of the Early Years landscape and its implications for parental involvement. The research draws upon the voices of both parents and professionals, with interviews conducted across four settings with different educational ethoses in one town. The participants typify the under-represented just about managing (May, 2016) class, which is neither rich nor poor. The focus on this group, living in a small deindustrialised town, provides an original contribution as both these populations and locations are under researched in the literature. In a progressively privatised and diverse market, parents must choose between childcare settings. However, the research findings demonstrate that they are unable to act as truly Neo-liberal, rational citizens because their decisions are influenced by emotions and human-interactions. The market landscape exemplifies a multiplicity of different ethoses around the education and care of the child which are communicated through the practice and provision in these individual settings. Conversations with parents and professionals explored the implications for children that stem from this diversity. This thesis has illustrated that parents choices impact even very young children, and thus proposes that the association between class and educational outcome starts prior to school age. The increasingly interventionist role of the state, accompanied by emphasis on parents to take responsibility for children s outcomes was examined. This illustrated the complex interplay of power shared by and between professionals and families as each sought to influence the other to achieve a shared vision of early education. This thesis has demonstrated that parents of even young children are expected to take an active role in their children s home learning in a way that was previously associated with older children. In doing so it has illustrated the challenge for Early Years settings in achieving levels of engagement that respect the individual capacity of each parent, based on their so-cial, cultural and financial capital. Regardless of their class position, this thesis showed that different techniques were employed by mothers, which demonstrate their ability to be powerful advocates for their children by influencing, and at times exploiting the Early Years work-force. In conclusion, the thesis highlights the three innovative contributions the research makes to: Geographies of Education; Geographies of Children, Youth and Families; and the Sociology of Education.